Congress and the Constitution - Whittington, Keith E.; Devins, Neal (Book collections on Project MUSE., 2005)
Essays contest notion of the absolute preeminence of judicial review in constitutional interpretation, analyzing the role of Congress as a constitutional interpreter and responsible constitutional agent.